2007
DOI: 10.1038/oby.2007.174
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss and Health Outcomes in African Americans and Whites After Gastric Bypass Surgery

Abstract: The objective was to describe differences in weight loss, dietary intake, and cardiovascular risk factors between white and African-American patients after gastric bypass (GBP). Research Methods and Procedures:This was a retrospective database review of a sample of 84 adult patients (24 African-American and 60 white women and men) between the ages of 33 and 53 years. All subjects had GBP surgery in 2001 at the Bariatric Surgery Program at Boston Medical Center in Boston, MA, and were followed for one year post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 37 publications
(46 reference statements)
3
42
0
1
Order By: Relevance
“…7,8 Moreover, limited available data suggest that bariatric surgery may be less effective among racial minorities. 28 There is less dispute about the effectiveness of bariatric surgery in men; however, the perioperative risk may be slightly higher than in women. 10,29 Nevertheless, improved discussions about the risks and benefits of bariatric surgery are likely warranted especially since high perceived risk is the most common deterrent cited by patients.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Moreover, limited available data suggest that bariatric surgery may be less effective among racial minorities. 28 There is less dispute about the effectiveness of bariatric surgery in men; however, the perioperative risk may be slightly higher than in women. 10,29 Nevertheless, improved discussions about the risks and benefits of bariatric surgery are likely warranted especially since high perceived risk is the most common deterrent cited by patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 Further, across multiple treatment modalities, including behavioral therapy and surgery, African Americans lose less weight than Caucasians. [2][3][4][5] Currently the United States Preventive Services Task Force (USPSTF) recommends that clinicians screen all patients for obesity, defined as BMI ≥30 kg/m 2 , and provide intensive counseling on lifestyle and behavior modification to promote weight loss to overweight and obese patients. 6 Despite these recommendations, most data suggest that such counseling occurs in less than 20% of primary care visits.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Buffington et al [15] found that NHB adults had lesssuccessful weight outcomes after gastric bypass than did NHW adults. Among adults, NHB women lost considerably less weight after surgery than did NHW women [13][14][15][16] . Additionally, in the Netherlands, Admiraal et al [22] found that African, South Asian, Turkish and Moroccan patients lost less weight at 1-year post-gastric bypass surgery versus their ethnic Dutch counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies suggest that neither pharmacologic nor dietary treatment can maintain weight loss in obese adolescents as effectively as can weight-loss surgery [11,12] . Several studies have shown that among adults, weight loss outcomes after bariatric surgery differ by ethnicity with some studies reporting better outcomes among nonHispanic whites than among non-Hispanic blacks [13][14][15][16] . Although the literature on outcomes of bariatric surgery in adolescents has increased exponentially, many studies are small and usually from single institutional series [8] .…”
Section: Introductionmentioning
confidence: 99%